Monocyte or white blood cell counts and β2 microglobulin predict the durable efficacy of daratumumab with lenalidomide. (December 2022) - Shimazu, Yutaka; Kanda, Junya; Kaneko, Hitomi; Imada, Kazunori; Yamamura, Ryosuke; Kosugi, Satoru; Shimura, Yuji; Ito, Tomoki; Fuchida, Shin-ichi; Uchiyama, Hitoji; Fukushima, Kentaro; Yoshihara, Satoshi; et al.
Background: Daratumumab is one of the most widely used treatments for relapsed/refractory multiple myeloma (MM) patients. However, not all patients achieve a lasting therapeutic response with daratumumab. Objectives: We hypothesized that a durable response to daratumumab could be predicted by the balance between the MM tumor burden and host immune status. Design: We conducted a retrospective study using the real-world data in the Kansai Myeloma Forum (KMF) database. Methods: We retrospectively analyzed 324 relapsed/refractory MM patients who were treated with daratumumab in the KMF database. Results: In this study, 196 patients were treated with daratumumab, lenalidomide, and dexamethasone (DLd) regimen and 128 patients were treated with daratumumab, bortezomib, and dexamethasone (DBd) regimen. The median age at treatment, number of prior treatment regimens and time-to-next-treatment (TTNT) were 68, 4 and 8.02 months, respectively. A multivariate analysis showed that the TTNT under the DLd regimen was longer with either higher monocyte counts (analysis 1), higher white blood cell (WBC) counts (analysis 2), lower β2 microglobulin (B2MG < 5.5 mg/L) or fewer prior regimens (<4). No parameters were correlated with TTNT under the DBd regimen. Conclusion: We propose a simple scoring model to predict a durable effect of the DLd regimen by classifying patients into three categories based on either monocyte counts (0 points for ⩾200/μl; 1 point for <200/μl) or WBC counts (0 points for ⩾3500/μl; 1 point for <3500/μl) plus B2MG (0 points for <5.5 mg/L; 1 point for ⩾5.5 mg/L). Patients with a score of 0 showed significantly longer TTNT and significantly better survival compared to those with a score of 1 or 2 (both p < 0.001). To confirm this concept, our results will need to be validated in other cohorts.